IRDP a case study of Bikram block, Patna district (Bihar). - Bipin Kumar (1995)
"This paper examines the role of Integrated Rural Development Programme (IRDP) in alleviating the poverty and creating employment opportunities, the information is collected from villages of Patna district in Bihar through personal interview method. It is found that there are malpractices in identifying beneficiaries, sanction of loans and obtaining assets. This inadequacy in loan amount forced the beneficiaries to borrow from the rural moneylenders. Income generation through self-employment is far from satisfactory. Proper selection of beneficiaries, distribution of right type of assets and good monitoring and follow-up action are suggested making the scheme helpful to the rural community"
Keywords: Integrated Rural Development Programme; Poverty - India - Bihar - Case studies; Rural development - India - Bihar - Case studies